2019
DOI: 10.1039/c8bm01669k
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of organosilica-capped mesoporous silica nanocarriers with selective redox-triggered drug release properties for safe tumor chemotherapy

Abstract: We develop a facile route to synthesize organosilica-capped mesoporous silica nanocarriers for efficient and safe redox-triggered tumor chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Adapted with permission. [ 23 ] Copyright 2019, The Royal Society of Chemistry. E) Drug‐release mechanism of polycaprolactone/DOX‐loaded fluorescent mesoporous silica.…”
Section: Stimuli‐responsive Drug‐release Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Adapted with permission. [ 23 ] Copyright 2019, The Royal Society of Chemistry. E) Drug‐release mechanism of polycaprolactone/DOX‐loaded fluorescent mesoporous silica.…”
Section: Stimuli‐responsive Drug‐release Engineeringmentioning
confidence: 99%
“…With the rapid development of nanotechnology and biomedicine, drug delivery systems (DDSs) have been considered as the most practical and valuable targeted therapy strategy in diverse diseases, [ 1–8 ] such as cancer, [ 9–12 ] bone injury, [ 13–16 ] tissue defect, [ 17–19 ] infectious disease, [ 20 ] and so on. In terms of controlled drug release, the most critical part is the host functional nanocarrier, which enables to deliver guest therapeutic agents (e.g., doxorubicin (DOX), [ 6,21–23 ] ibuprofen, [ 24–26 ] alendronate, [ 27 ] gentamicin sulfate (GS), [ 28–31 ] or other anticancer drugs) and transfer to targeted cells or pathological tissues. These nanocarriers can precisely release drugs through stimuli‐responsive system to achieve a controllable and on‐demand therapy.…”
Section: Introductionmentioning
confidence: 99%
“…e silica monolayer was formed after MPTMS immobilization on the surface of gold nanoparticles and hydrolysis in basic media [22]. Shen et al have synthesized PEGylated capped MSNs and covered with MPTMS, to be used as a gatekeeper [23]. Cheng et al reported the functionalization of MSNs with pH-sensitive trimethylammonium as pH-controllable drug release [24].…”
Section: Introductionmentioning
confidence: 99%
“…[ 21 ] This method has been widely used in encapsulation and delivery of a variety of functionalities like, antitumor drugs, MRI CAs, and fluorescent dyes. [ 22 ] Wang et al have co‐assembled superparamagnetic iron oxide nanocrystals and conjugated polymers in organosilica cross‐linked micelles and achieved T 2 ‐weighted MRI and fluorescent bimodal imaging. [ 23 ]…”
Section: Introductionmentioning
confidence: 99%